A Trinuclear Defect‐Grid Iron(II) Spin Crossover Complex with a Large Hysteresis Loop that is Readily Silenced by Solvent Vapor1. (22nd May 2014) - Steinert, Markus; Schneider, Benjamin; Dechert, Sebastian; Demeshko, Serhiy; Meyer, Franc
Abstract A new type of [2×2] matrix‐like complexes with one vertex devoid of a metal ion has been selectively synthesized. The defect‐grid triiron(II) complex exhibits a sharp and complete spin‐crossover (SCO) from the 1HS‐2LS to the 2HS‐1LS state (HS: high spin; LS: low spin) with wide hysteresis near room temperature. Although the "structurally soft" H‐bonded vertex, elastically coupled to the metal ions, accounts for the stabilization of spin states, it also mediates a dramatic, yet reversible, response to the uptake of exogenous solvent molecules leading to silencing of the SCO. The high sensitivity towards those guest molecules, the short response time upon exposure, and the smooth reversibility of guest binding are favorable characteristics for future sensing applications of such defect grids.